The transcriptomic footprint of Mytella strigata: de novo transcriptome assembly of a major invasive species - V. G. Vysakh; Sandhya Sukumaran; Wilson Sebastian; A. Gopalakrishnan (Scientific Data)
Abstract Mytella strigata, a potentially invasive species native to South America, is rapidly spreading across various aquatic ecosystems around the globe, posing a threat to native mussels. This study presents the first comprehensive de novo transcriptome assembly of M. strigata. We generated 254 million reads, which were processed and assembled using the Trinity assembler, resulting in 60362 transcripts with an N50 of 1,578 bp and over 93–98% completeness, as confirmed by BUSCO analysis with multiple ortho-datasets. A number of databases were used for functional annotation, including UniProt, KEGG, Reactome, InterPro, and eggNOG. Gene Ontology and pathway analyses identified transcripts associated with key biological processes, including those associated with cell signalling, metabolism, stress responses, cancer pathways, and immune regulation. This dataset enriches the bivalve database by advancing the understanding of the adaptive success and evolutionary resilience of this invasive species. The present study provides a fundamental framework for future research on the ecological and evolutionary impacts of this invasive species.